sLORETA Source Localization in Dyslexic Children during Different Congruency of Visual Images: P300 Component Analysis (Sumber aktiviti sLORETA dalam kalangan Kanak-kanak Disleksia dalam Stimulasi Imej Visual yang Berbeza Kesesuaian Konteks: Komponen P300 Analisis) - Siti Atiyah, Ali; Siti Atiyah, Ali; Faruque, Reza; Tahamina, Begum; Nor Asyikin, Fadzil; Faiz, Mustafar (Penerbit UKM (UKM Press), 2020)
The question of whether dyslexic children have visual cognitive differences in terms of brain activity as compared to normal children remains unsolved. Here, we aimed to study the neuronal source activity during visual attentional processing reflected in the P300 Event-Related Potential (ERP) component, when being exposed to the different congruency of visual images on dyslexic children by utilizing an ERP. Twelve dyslexic and twelve non-dyslexic children in the range of age 8 to 11 years old took part in this study. They pressed button ‘1’ when they saw a congruence image of the animal in its natural habitat and button ‘2’ for incongruence animal images in non-natural habitat. The source localization of P300 was executed on the grand average waveform by utilising Standardised Low-Resolution Brain Electromagnetic Tomography (sLORETA) algorithm provided by Net Station software. The BA 19 of the left occipital lobe was the most activated during congruence and incongruence images in the dyslexic children. As for the control children, BA 18 and BA 17 of the occipital lobe were activated during congruence and incongruence images, respectively. In sum, there were no differences in source activity areas during both visual images in dyslexic children as compared to the control children, which brings us to a conclusion that the visual attentional activity in dyslexic children used the brain areas that are associated with visual characteristics rather than context differences.